Management of rectal stump leak following emergency Hartmann’s procedure - Johnston, Sarah; De Lacavalerie, Penelope (Journal of Coloproctology, 2020)
We report on the management of three cases of rectal stump leak and sepsis following urgent Hartmann’s procedure for perforated sigmoid diverticulitis or large bowel obstruction. Two patients had significant risk factors for poor tissue healing. All patients developed features of sepsis and computer tomography scans demonstrated rectal stump leak with adjacent collections. All patients required reoperation for drainage and washout of abscess. An intraperitoneal catheter system was introduced together with drains in order to continue on the ward until tract was formed. There was no mortality and minimal morbidity. The key to management of rectal stump leak is the early and aggressive drainage of the associated collection and continued irrigation of the stump.
Keywords: Hartmann’s procedure; Rectal stump leak; Post-operative complication; Sepsis